Tinjauan Metodologi dan Etika Penelitian Pendidikan: Kuantitatif, Kualitatif, dan Metode Campuran - Tedi Priatna; Bayu Bambang Nur Fauzi; Dian Febriyanti; Ilham Hidayatul Ramadhani; M. Rafi Gastiadirrijal; Nabila Putri Aulia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article aims to comprehensively review the basics of educational research including quantitative, qualitative, mixed methods research, as well as research ethics. Using the methods of literature study and content analysis, the realities of educational research are decomposed through a conceptual review. The results of the study show that the quantitative approach is based on the philosophy of positivism, focuses on the measurement of numbers, and produces cause-and-effect generalizations. Qualitative research is grounded in constructivism, emphasizes on understanding deep meaning, and is narratively descriptive in nature. Meanwhile, mixed methods integrate both approaches to find practical solutions. Research ethics demands that researchers uphold scientific honesty, objectivity, and respect participants’ rights, such as informed consent and data confidentiality. A strong understanding of these fundamentals is essential for prospective educators, particularly PAI students, as a provision for scholarly skills in both academic and teaching practice